On a New Iterative Scheme without Memory with Optimal Eighth Order - M. Sharifi; S. Karimi Vanani; F. Khaksar Haghani; M. Arab; S. Shateyi (The Scientific World Journal)
The purpose of this paper is to derive and discuss a three-step iterative expression for solving nonlinear equations. In fact, we derive a derivative-free form for one of the existing optimal eighth-order methods and preserve its convergence order. Theoretical results will be upheld by numerical experiments.